2018
DOI: 10.1017/s0031182018000665
|View full text |Cite
|
Sign up to set email alerts
|

Host community heterogeneity and the expression of host specificity in avian haemosporidia in the Western Cape, South Africa

Abstract: Similar patterns of parasite prevalence in animal communities may be driven by a range of different mechanisms. The influences of host heterogeneity and host-parasite interactions in host community assemblages are poorly understood. We sampled birds at 27 wetlands in South Africa to compare four hypotheses explaining how host community heterogeneity influences host specificity in avian haemosporidia communities: the host-neutral hypothesis, the super-spreader hypothesis, the host specialist hypothesis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, regarding malaria parasite evenness, we found that different lineages were more evenly distributed in Southwest Amazon moist forests, in addition to the Sechura desert and Peruvian Yungas. On the contrary, Iquitos várzea and Ucayali moist forests revealed a less homogeneous parasite community, which could be related to the parasite strategies (specialists–generalists) in heterogeneous host communities ( Jones et al 2018 ). Regarding the composition and richness of parasite communities, we have obtained similar results to those shown by Lacorte et al (2013) , who found the same pattern for both bird and parasite communities.…”
Section: Discussionmentioning
confidence: 98%
“…However, regarding malaria parasite evenness, we found that different lineages were more evenly distributed in Southwest Amazon moist forests, in addition to the Sechura desert and Peruvian Yungas. On the contrary, Iquitos várzea and Ucayali moist forests revealed a less homogeneous parasite community, which could be related to the parasite strategies (specialists–generalists) in heterogeneous host communities ( Jones et al 2018 ). Regarding the composition and richness of parasite communities, we have obtained similar results to those shown by Lacorte et al (2013) , who found the same pattern for both bird and parasite communities.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we found that different lineages were more evenly distributed in urban areas, while those of hill areas and paddy fields had a more heterogeneous parasite community, which could be related to the parasite strategies (specialists-generalists) in heterogeneous host communities [122]. Evenness is, therefore, an important factor to consider when analyzing communities since it may give a general sense about how parasite lineages or host species are distributed among different areas [123].…”
Section: Anthropic Disturbance and Avian Haemosporidian Infectionmentioning
confidence: 90%
“…Plasmodium lineage Swa43 ( Table S3 ) which was incidentally recovered from brood-parasitic Long-tailed Paradise Whydah ( Vidua paradisaea ) and Dusky Indigobird ( Vidua funerea ) commonly infected Village Weavers and other species of Ploceidae. This conclusion is further supported by evidence from avian communities in South Africa where Plasmodium parasites were characterized by a wide host-breadth ( Jones et al, 2018 ). However, some Haemoproteus and Leucocytozoon lineages (Swa61 and Swa09, respectively) were exclusively recovered in Viduidae, suggesting that low prevalence in these genera may not be produced by the loss of host-specific parasite lineages.…”
Section: Discussionmentioning
confidence: 55%
“…Another possible explanation for the low observed prevalence of haemosporidia in Viduidae compared to other host species examined in this study is their low population densities within savanna ecosystems in northeastern Eswatini ( Monadjem, 2005 ). Host density has been shown to significantly affect the propagation of pathogens through host communities, where common species may be characterized by increased contact rates that ultimately result in a higher observed prevalence than rare species ( Ellis et al, 2017 ; Jones et al, 2018 ). However, Fecchio et al (2017) did not find a correlation between host density and prevalence of Plasmodium in avian assemblages in southern Amazonia.…”
Section: Discussionmentioning
confidence: 99%